Plato’s Apology as Forensic Oratory - Tennant, John Roger (Revista Archai, 2015)
This article recasts Plato’s Apology of Socrates as a piece of forensic oratory. By examining the rhetorical topoi utilized by Plato, I intend to demonstrate how Plato pushes the boundaries of the genre of forensic oratory toward the creation of a new discursive practice: philosophy. The article first examines the concept of “genre” in connection with forensic oratory. Drawing upon the work of Mikhail Bakhtin, Tzvetan Todorov, and Andrea Nightingale, the article establishes a consonance between these scholars’ conceptions of genre and what other scholars have defined as the “genre” of forensic oratory. The article then takes up the question of why Plato’s Apology traditionally has been excluded from this genre. I argue that certain views concerning the presumed historicity of speeches awarded the label of “forensic oratory” need to be reexamined, as there is no clear evidence that the Athenians required historical accuracy of the speeches we now classify as forensic oratory. By removing the requirement of historicity, we gain a more accurate picture of what constitutes forensic oratory and why Plato’s Apology deserves membership in this genre. The article then examines in detail various rhetorical topoi in the Apology. I argue that by manipulating and reworking such topoi, Plato expands and redefines the genre of forensic oratory to include the new discursive practice of philosophy. The article reveals how Plato’s redefinition of the boundaries of forensic oratory transformed a criminal defendant’s speech in a court of law into the sine qua non of the philosopher and the philosophic life.